O sertão encantado pelo aedo Elomar : metáforas da saudade - Silva, Tatiana Cíntia da (2014)
Our work of literary criticism is concerned with the intertextual relation proposed in the work of Elomar from the analytical study of some lyrics of his songs which we consider representative of the dialogue between the troubadour lyric and culture of the northeast. For this comparative study, we have chosen as our corpus these following songs by Elomar Figueira Mello: Campo Branco, Cantiga de Amigo, Cantiga de Boi Encantado, Cantiga de Estradar, Incelença pro Amor Retirante, O Rapto de Joana do Tarugo, O Violêro e Retirada, which will be contemplated from intertextuality, imaginary, identity and memory, both singing backcountry and the medieval trovar. This study, then, will take care of dialogue O Sertão Encantado pelo Aedo Elomar: Metafóras da Saudade, starting from the points of contact and separation between the two lyrical then seizing the representations of an ox enchanted by many cultures and the construction of a cowboy hero and, finally, it thinks about the movement of removal of backlands not only because of the drought, as if the interior has been just a place to struggle to survival and suffering, but also, and mainly, as a place of nostalgia, beauty, memory, myth, family rigors, ethics and religiosity. In this singing, we will highlight the metapoetics character of aedo sertanejo, who has property in his singing and is polyglot in "sertaneza" language. For the highlights, we will consult theorists and researchers from intertextual field, mention Mikhail Bakhtin; about the importance of identity, memory, relationship, literature, society and culture, we will highlight Roger Chartier; for the study of medieval literature, José Saraiva; on the backcountry, Durval Muniz; and we’ve consulted critical studies about Elomar.